Nucleus‐Targeted Delivery of Multi‐Protein Self‐Assembly for Combined Anticancer Therapy. Issue 25 (24th May 2021) - Tang, Jiakun; Liu, Ye; Qi, Dongmei; Yang, Lan; Chen, Hui; Wang, Chenhui; Feng, Xuli
Abstract: Protein therapy has the potential to revolutionize medicine, but the delivery of multiple proteins is challenging because it requires the development of a strategy that enables different proteins to be combined together and transported not only into cells, but also to the desired cell compartments, such as the nucleus. Here, an efficient intranuclear protein delivery nanoplatform based on modified ribonuclease A (RNase A) tuned self‐assembly is presented. RNase A bioreversibly modified with adamantane is functionalized with wind chime‐like lysine modified cyclodextrin (WLC) to generate RNase A‐WLC (R‐WLC). R‐WLC can not only enhance the cellular uptake of RNase A and accumulate it into the nucleus, but also works as nanovehicles to efficiently transport deoxyribonuclease I (DNase I) into the nucleus, resulting in greatly improved antitumor efficacy in vitro and in vivo. This protein co‐assembly strategy can be applied to other functional proteins and has great prospects in the treatment of many diseases. Abstract : Highly efficient nucleus‐targeted delivery of multi‐protein self‐assembly nanoplatform for combined anticancer therapy has been prepared. The assembled nanoproteins with high protein loading efficiency and endosomal escape ability show enhanced cellular uptake and accumulation in the nucleus, resulting in greatly improved anti‐tumor efficacy of RNase A and DNase I both in vitro and in vivo.